Mitigative role of cysteamine against unilateral renal reperfusion injury in Wistar rats - Alabi, Babatunde Adebola; Nku-Ekpang, Okot-Asi; Lawal, Sodiq Kolawole; Iwalewa, Ezekiel Olugbenga; Omobowale, Temidayo; Ajike, Richard; Lawal, Ridwan Abiodun (Frontiers in Pharmacology, 2024)
Background: Ischemia-reperfusion injury (IRI) is unavoidable during kidney transplant and it is responsible for delayed or non-function after kidney transplantation. Cysteamine is the standard drug in the management of nephropathic cystinosis and its extra-renal complications. Thus, we designed this study to investigate its potential against renal reperfusion injury.Results: Significant elevation of H2O2, MDA, and nitrite and reduced GPx, GSH, and protein thiol in the IRI rats was reversed by cysteamine (50 and 100 mg/kg). Serum MPO, TNF-α, IL-1β, creatinine, and AOPP were significantly elevated in IRI while rats treated with cysteamine revealed a significant decrease (p<0.05) in the activities of these pro-inflammatory and renal injury markers.Based on its activity against inflammation, apoptosis, and free radical-induced stress, cysteamine has great potential to be used as a kidney transplant pre-operative drug to prevent renal reperfusion injury.